Synergistic alleviation effects of salt-tolerant plant growth-promoting rhizobacteria and hydrogen-rich water on salt stress in Pennisetum giganteum - Chu, Shaohua; Xu, Ting; Feng, Yuying; Ma, Xianzhong; Shu, Ruitian; Wang, Renyuan; Wang, Yu; Jin, Doudou; Chi, Yaowei; Zhou, Pei; Zhang, Dan (Frontiers in Plant Science, 2025)
Soil salinization severely restricts agricultural production and the sustainable use of soil. While plant growth-promoting rhizobacteria (PGPR) and hydrogen-rich water (HRW) have individually been reported to alleviate salt tolerance, their synergistic effects and molecular mechanisms remain largely unexplored. In this study, we investigated the combined application of a salt-tolerant PGPR strain Cytobacillus firmus L71 and HRW in Pennisetum giganteum under NaCl stress. A factorial pot experiment was conducted under three salt levels (0, 250, and 500 mM NaCl) with or without PGPR-HRW treatment. Growth traits, antioxidant activities, osmotic regulators, and transcriptomic responses were measured. The combined treatment significantly promoted growth under severe salinity, with shoot fresh weight increasing by 148% and root length by 54.60% compared with untreated control. Physiological measurements showed elevated activities of Superoxide Dismutase (SOD), Peroxidase (POD), and Catalase (CAT), and reduced accumulation of Malondialdehyde (MDA) and Hydrogen peroxide (H2O2). Transcriptome analysis indicated consistent enrichment in plant hormone signaling, mitogen-activated protein kinase (MAPK) signaling, and plant-pathogen interaction pathways. Negative regulators such as CaM/CML (induces stomatal closure), CDPK (triggers hypersensitive response), WRKY25/33 (inhibits DNA defense genes), and JAZ (accelerates stress-induced senescence) were down-regulated, while positive regulators including A-ARR (enhances cell division and shoot growth) were up-regulated, contributing to sustained stomatal function, delayed senescence, and improved reactive oxygen species (ROS) balance. These results demonstrate that PGPR-HRW synergy enhances salt tolerance through coordinated physiological and transcriptional regulation, highlighting the potential of integrating microbial inoculants with HRW for sustainable saline soil remediation and crop improvement.